Transparansi Penggunaan Dana Bos di Sekolah Dasar Islam Terpadu Muhammadiyah - Teguh Waluyo; Harsono .; Suyatmini . (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This research was conducted to describe the transparent use of BOS funds at SD IT Muhammadiyah The principles of managing BOS funds include planning, implementing, monitoring, and evaluating, as well as BOS reporting. This study used a qualitative approach, using a study research library technique. Sources of research data were obtained from interviews with school principals, BOS treasurers, school committees, and teachers. As reinforcement is equipped with observations and documentation. The management of School Operational Assistance (BOS) funds at SD IT Muhmammadiyah is based on the principles of flexibility, effectiveness, efficiency, accountability, and transparency. This is reflected in the planning of BOS funds at SD IT Muhammadiyah carried out in accordance with procedures and technical guidelines. The use of BOS funds was adjusted according to priority needs. From the point of view of good supervision, this is indicated by the results of internal and external audits so that no misuse of budget funds was found.